An Allocation Model for Catalog Space Planning - Johnson, Miki; Zoltners, Andris A.; Sinha, Prabhakant (Management Science, 1979)
Deciding which items to include in a sales catalog and how much space should be allocated to each item is a major planning problem facing many large retailers and catalog firms. The steps in the catalog planning process include compiling a list of candidate items, developing one or several ad size “strategies” for each item, estimating the sales and contribution which would be realized as a result of each strategy, and then selecting a set of strategies which effectively allocate the space available in the catalog to some subset of items. This paper describes the planning process in detail. An integer programming model is presented which incorporates merchandising policy constraints in optimally choosing the items and ad strategies to be included in the catalog. The organizational implications of using such a model are also explored. A simple example of the application of the model to planning the tennis equipment lines of a major mass merchandiser appears as an appendix.